Characteristics research on sewage sludge under thin-layered hot-press treatment. Issue 44 (19th September 2016) - Wang, Weiyun; Liu, Wanyu; Wang, Lingyun
Abstract: Thin-layer thermal pressing is an innovative method that has the potential to further eliminate moisture content in liquid form from mechanical dewatering of sludge. Here, the dewatering performances of treated sludge are evaluated. The results demonstrate that the hot-press treatment is able to effectively reduce the moisture content of dewatered sludge with a thickness of less than 5 mm. A preliminary survey of the hot-press mechanisms for thin-layer sludge has also been conducted, by analysis of extracellular polymeric substance extracted from treated sludge. It can be deduced that hot pressing leads to cell damage in sludge by increased cell lysis.